Theimpact of procedural knowledge on job burnout within hotel organizations: A case study on hotels in Baghdad (International Journal of Psychosocial Rehabilitation, 2020)
This study came to clarify the psychological conditions experienced by workers in various Iraqi hotels as a result of exposure to routine work pressures and the associated effects on the level of performance and their relationship to management, which adversely affects the nature of the organization It is also necessary to review all the means and procedures followed in the manner of performing the various acts and work to remove what is unnecessary and simplify these procedures and work to apply the procedural knowledge in a manner appropriate to the nature of the work entrusted to the perpetrators, which distancing workers from the atmosphere of psychological pressure and to do business more flexible and away from the phenomenon job burnout This study included three chapters based on the main variables that are guaranteed, namely procedural knowledge as well as burnout. The problem of study is to exaggerate the pattern in dealing with individuals working in hotel organizations and there is no doubt that most of the hotel organizations have detailed laws and regulations governing the nature of the work and thus these stereotypes have a significant impact on the emergence of the phenomenon of burnout of employment The study aims to achieve a set of objectives, including identifying the factors that cause the phenomenon of burnout of working and work to reduce them, as well as knowledge of the relationship between the practices for procedural knowledge and the process of burnout in the functional hotel organizations To know the level of psychological pressure among workers in hotel organizations The study was able to come up with a set of conclusions and recommendations aimed at identifying the real causes and the most impact on the workers and then develop appropriate solutions through some recommendations